Development of a Mobile Application for Indigenous Language Learning: Mazahua and Hñähñu - Castillo Alarcon, I.; Sampedro Mendoza, A.; Cásares García, L.; Franco Árcega, A.; Cruz Olguín, J. M.; Ojeda Misses, M. A. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
This paper presents the development of a mobile application that provides university students with access to learning resources for the indigenous languages Mazahua and Hñähñu. The mobile application is designed as an accessible digital tool that integrates a translator based on Transformer models for body-part vocabulary and a card-based game that combines a memory game and a puzzle, incorporating augmented reality featuring animals. The application was developed in collaboration with computer science and linguistic-cultural experts to ensure accuracy and relevance in the indigenous languages. The application aims to encourage vocabulary learning related to body parts and animals, while supporting writing and pronunciation through interactive games. Finally, the application was evaluated with university students, which demonstrated their motivation to participate and the application’s success in promoting the learning of indigenous languages through the use of accessible technology, especially in geographic areas where these languages are declining.